1999
DOI: 10.1086/307646
|View full text |Cite
|
Sign up to set email alerts
|

Small‐Scale Anisotropy of Cosmic Rays above 1019eV Observed with the Akeno Giant Air Shower Array

Abstract: With the Akeno Giant Air Shower Array, 581 cosmic rays above 1019 eV, 47 above 4 ] 1019 eV, and seven above 1020 eV were observed until 1998 August. The arrival direction distribution of these extremely high energy cosmic rays has been studied. While no signiÐcant large-scale anisotropy is found on the celestial sphere, some interesting clusters of cosmic rays are observed. Above 4 ] 1019 eV, there are one triplet and three doublets within a separation angle of and the probability of observing 2¡ .5, these clu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
172
2
3

Year Published

2002
2002
2008
2008

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 383 publications
(187 citation statements)
references
References 45 publications
10
172
2
3
Order By: Relevance
“…27 (3) random samples had a probability of less than 10 −2 (10 −3 ), and the authors concluded that the correction factor was of order 3. The final chance probability was given as 3 · 10 −4 , considerably lower than the chance probability reported by the AGASA collaboration in the original publications [2,3].…”
Section: Small Scale Clustering In Agasa Cosmic Ray Datamentioning
confidence: 61%
See 4 more Smart Citations
“…27 (3) random samples had a probability of less than 10 −2 (10 −3 ), and the authors concluded that the correction factor was of order 3. The final chance probability was given as 3 · 10 −4 , considerably lower than the chance probability reported by the AGASA collaboration in the original publications [2,3].…”
Section: Small Scale Clustering In Agasa Cosmic Ray Datamentioning
confidence: 61%
“…The AGASA experiment reported possible clustering in the arrival directions of ultrahigh energy cosmic rays as early as 1996 [2], and has updated this data sample and analysis in several publications [3][4][5][6]. The first report of clustering in 1996 identified three pairs of events with angular separation less than 2.5 • among the 36 events with energies above 4 · 10 19 eV.…”
Section: Small Scale Clustering In Agasa Cosmic Ray Datamentioning
confidence: 99%
See 3 more Smart Citations